Effect of Acid Marination Assisted by Power Ultrasound on the Quality of Rabbit Meat - Julián Andrés Gómez-Salazar; Diana A. Ochoa-Montes; Abel Cerón-García; César Ozuna; Maria Elena Sosa-Morales (Journal of Food Quality)
The consumption of rabbit meat is scarce in Mexico, despite its good taste and high protein content. Acid marination may be an option to introduce this meat into new markets and add value to this food. The use of ultrasound has been reported as an accelerator in the impregnation process and improving the product quality. The objective of this study was to evaluate the effect of acid marination assisted by power ultrasound on quality of rabbit meat. Marinating solutions were prepared with 70, 140, or 200 g NaCl/L, 3 g NaNO2, and 1.5% citric acid. Rabbit meat slices were immersed in every solution in static and ultrasonic bath at 40 kHz and 110 W of output power. Marinating time, NaCl concentration in the marinating solution, and US application increased weight losses and meat hardness but reduced water content, WHC, and pH. The color parameters L⁎ and a⁎ increased with the NaCl concentration in marinating solution and with the ultrasound application. NaCl content increased in meat with increased marinating time, NaCl concentration in marinating solutions, and higher rate in ultrasonic treatment. Application of ultrasound has high potential to be employed in the marinating of rabbit meat samples, diminishing the immersion time, and maintaining the quality.